2021
DOI: 10.1111/jocs.15526
|View full text |Cite
|
Sign up to set email alerts
|

Increased number of ventricular septal rupture cases after acute myocardial infarction in 2020

Abstract: Introduction: Ventricular septal rupture (VSR) is a serious mechanical complication after acute coronary syndrome and is related to high mortality. Even with advances in the management of acute myocardial infarction (AMI) such as reperfusion therapies, complication rates are still high. During quarantine, patients presenting mechanical complications after AMI have increased in our institution.Methods: From a retrospective database analysis in our institution between the years 2004 and 2020, we identified 37 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Furthermore, in that review, the mortality rate for VSR was as high as 54.6% [ 3 ]. A comparable trend was demonstrated by data from another institution, whereby, with the onset of the COVID-19 pandemic, the average number of operations for VSR increased to 4 cases/year, having been as low as 1.9 cases/year in previous years [ 4 ].…”
supporting
confidence: 67%
“…Furthermore, in that review, the mortality rate for VSR was as high as 54.6% [ 3 ]. A comparable trend was demonstrated by data from another institution, whereby, with the onset of the COVID-19 pandemic, the average number of operations for VSR increased to 4 cases/year, having been as low as 1.9 cases/year in previous years [ 4 ].…”
supporting
confidence: 67%
“…A large number of operations were canceled or postponed due to interruptions caused by COVID‐19. Coincidentally, our institution have reported an increased number of mechanical complications, that maybe related to decreased number of patients seeking for medical assistance 16 …”
mentioning
confidence: 89%
“…Coincidentally, our institution have reported an increased number of mechanical complications, that maybe related to decreased number of patients seeking for medical assistance. 16 Studies conducted in the first months of the pandemic showed that if countries increased their normal surgical volume by 20%, it would take an average of 45 weeks to balance the backlog of operations resulting from the interruption of COVID-19. 9 Patients awaiting elective cardiac surgery need to be proactively managed, reprioritizing those with high-risk anatomy or whose clinical status is deteriorating.…”
mentioning
confidence: 99%
“…Moreover, only one patient got COVID-19 infection during hospital stay, that later represented the cause of death. Therefore, despite the sometimes-advocated fear of getting COVID-19 on hospitalization during the pandemic peak, it is reasonable to conclude that, with proper safety measures, quickly reaching a tertiary centre in the presence of complicated AMI, does not represent an additional risk for hospital-acquired infection [ 9 ].…”
Section: Discussionmentioning
confidence: 99%